Financial Inclusion and Socio-Economic Development: Analysis Through The Banking Sector in India - Sharma , Shaveta; Pandey , Dr. Abhishek; Dr. Usha (International Journal of Accounting and Economics Studies, 2025)
Financial inclusion, a crucial aspect of economic development, aims to ensure that all members of an economy can access and effectively use appropriate financial services. This reduces poverty and enhances the country's financial well-being and economic development. The paper evaluates the impact of financial inclusion on customers' socio-economic development, offering a promising outlook for a more prosperous life. The policies on financial inclusion have garnered significant attention from scholars, policymakers, and regulators, as they have been theoretically acknowledged to affect socio-economic growth positively. The paper also provides recommendations for the governments of developing countries to enhance financial inclusion, inspiring hope for a more sustainable future.